Teacher–child relationships, interactions, and culturally inclusive pedagogy: A study on pre- and in-service early childhood education teachers in Finland - Yang, Wenwen (fi=Turun yliopisto|en=University of Turku|, 2024)
The purpose of this thesis is to develop valid and reliable assessment tools to examine and foster Finnish early childhood education (ECE) teachers’ professional development from the undergraduate level onwards and to improve the effectiveness of ECE teacher training programs. Three major theoretical concepts in this thesis were explored: teacher–child relationships, self-efficacy of culturally inclusive pedagogy, and teacher–child interaction, which are aligned with the key competence domains specified by the multidimensional adapted process model of teaching in educational context (MAP). Participants were ECE student teachers from a university bachelor’s degree program and qualified ECE teachers working in daycare centers in Finland. This study adopted a mixed methods approach consisting of statistical analyses for questionnaire data and systematic video observations. This thesis is comprised of three empirical studies. Study I validated the factorial validity and measurement invariance of the modified version of the Student–Teacher Relationship Scale-Short Form (STRS-SF) to investigate ECE student teachers’ and qualified teachers’ perceptions of closeness and conflict in their overall relationships with children. Multi-group confirmatory factor analyses (CFA) confirmed the closeness and conflict factors of the two-factor structure. ECE student teachers and two qualified ECE teacher groups reported overall high levels of close and low levels of conflictual relationships with children. Perceptional differences were demonstrated among groups of teachers at various career stages. Qualified teachers who voluntarily participated in training to enhance their professional skills perceived their relationships with children as having more conflicts. Student teachers reported fewer conflicts than qualified teachers enrolled in training and perceived less closeness compared to qualified teachers not attending training. This study extends the application of the STRS-SF in a Finnish educational context. Study II developed a new scale, Culturally Inclusive Pedagogy (CIP), for assessing ECE student teachers’ and qualified teachers’ self-efficacy beliefs in planning and implementing culturally inclusive pedagogy with diverse children. The CFA results revealed that CIP is a one-factor structure scale, and pre- and in-service ECE teachers’ self-efficacy beliefs were overall high at the construct level. At the item level, qualified teachers reported higher levels of efficacy than student teachers. The reciprocal relations between high self-efficacy of inclusive practices and self-perceived close teacher–child relationships were found among both student teachers and qualified teachers. The concurrent validity evidence implies the need for integrating training about relational processes and inclusive pedagogy into curriculum design for both pre- and in-service teachers. Study III aimed at evaluating the observed quality of ECE student teacher–child reading interactions and fostering student teachers’ pedagogical competence in higher education setting. The students were provided with a study module which consists of lectures about the knowledge of child development and ECE pedagogy, and tutorials as well as practices for identifying, implementing, and reflecting on high-quality interactions with children. The video-recorded one-on-two joint picture book reading interactions were assessed by the observational tool Classroom Assessment Scoring System (CLASS) Pre-K. The domain level analyses showed the imbalanced pattern of student teachers’ high quality of emotional support and classroom organization but low quality of instructional support. The behavioral level analyses indicated that student teachers primarily asked simple questions but rarely asked complex questions or provided extensive feedback to promote children’s higher-order thinking and language use. The results further showed that student teachers’ self-reported closeness with children improved and conflict decreased after the study module. This study highlights the importance of fostering higher-quality instructional support in teacher preparation programs and improving the effectiveness of university degree programs. Taken together, this dissertation contributes to the innovative use of research-based self-assessment and observation tools in the Finnish ECE context, allowing for further valuable cross-cultural comparison studies. Moreover, the utilization of these tools in Finnish teacher training programs provides practical significance for fostering teachers’ professional development.